Analysis of Students’ Errors and Writing Flow In Example Paragraph Written By The First Semester Students of English Department At The University of Mataram - Zahira, Sabrina; Thohir, Lalu; Putera, Lalu Jaswadi; Saputra, Agus (Journal of Authentic Research, 2025)
This study investigates the types and causes of grammatical errors found in example paragraph writing by first-semester students of the English Education Program at the University of Mataram during the 2024/2025 academic year. The participants were fifteen low-achieving students with beginner to intermediate levels of English proficiency, as determined by their writing course scores. The research employed a descriptive qualitative design, as this approach enabled the researcher to describe and interpret the data in depth without numerical generalization (Creswell, 2018). Data were collected from students’ written paragraphs and semi-structured interviews to explore both linguistic difficulties and cognitive causes of errors. Findings revealed 22 total errors, with misformation (45.4%) as the most dominant type, followed by omission (31.8%), misordering (13.7%), and addition (9.1%). The main sources of errors were translation habits, first language interference, and carelessness. These findings theoretically support interlanguage and error analysis theories, indicating that learner errors represent natural stages of language development. The study contributes to EFL writing pedagogy by emphasizing the importance of guided grammar practice, peer-editing, and continuous feedback to enhance students’ grammatical accuracy and coherence in example paragraph writing.